Low speed aerodynamic characteristics of 60 degrees rounded leading-edge delta wing with vortex flaps - Rinoie, K. (Cranfield University, 1996)
Low speed wind tunnel studies have been conducted to investigate the effect of vortex flaps with a rounded leading-edge on delta wing performance. Measurements were done using the 60º delta wing at a Reynolds number based on the centre line chord 8x10(5). Results indicated that the rounded leading-edge delta wing with 30º vortex flap deflection improves the lift/drag ratio at lift coefficients higher than 0.4, when compared with the sharp leading-edge flat delta wing. The effect of a trailing-edge flap with vortex flaps was also investigated.